Pelaksanaan Kewajiban Pengembang dalam Penyediaan Fasilitas Umum dan Fasilitas Sosial Perumahan di Kabupaten Badung - I Wayan Aditya Indrayana; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
The demand for the availability of housing needed to support the primary needs of the community, especially in the Badung Regency also continues to increase. However, the fact is that the housing development process is often not accompanied by adequate social facilities. There is a problem formulation, namely how to implement the developer's obligations in providing social facilities in Badung Regency housing and what are the obstacles to implementing the developer's obligations in providing social facilities in Badung Regency housing. The purpose of this study was to determine the implementation and development barriers. The method used in this research is empirical. There are still developers who have not fully provided social facilities in accordance with the regulations. In the provision of social facilities in Badung Regency are still several obstacles such as internal and external. The conclusion that can be drawn from this paper is that developers in Badung Regency have not fully carried out their obligations to build facilities in accordance with the site plan. the authors suggest implementing the developer's obligations in providing social facilities to run in accordance with the law, the government must carry out supervision and guidance for developers.